Photosynthetic Functioning As A Selection Criteria For Maximum Yield Potential In Some Wheat Genotypes Under Late Planting Heat Stress Conditions. - and Thind S K, Radhika* (International Journal of Scientific Research and Management (IJSRM), 2017)
Heat stress had profound effect on the photosynthetic efficiency. This study demonstrated a large degree of genotypicvariability in net photosynthesis, stomatal conductance and rate of transpiration among 40 wheat genotypes afteranthesis under late planting high temperature field conditions when compared with the timely sown. CTD measured inthe flag leaf was significantly correlated with grain yield when measured after anthesis, with correlation coefficients of0.389* (P